Retention curves and available water capacity in latosols - Maia, Felipe C. de O. (2018)
Water stored in the soil between field capacity and the permanent wilting point, is known as the available water capacity. Its availability to be effectively used by plants depends on the type of soil and its water retention characteristics. The aim of this work was to compile information about water retention curves in Latosols, and to provide a first approximation of values and most likely amplitudes for water storage and available water capacity of these soils. The database was constituted from information collected from articles, theses, dissertations and other publications. Soil water retention curves, as well as available water, were estimated for the order Latosols, and for the suborders Red Latosol (RL), Red-Yellow Latosol (RYL) and Yellow Latosol (YL). RL presented the lowest amplitude of water storage between field capacity and permanent wilting point, resulting in lower available water capacity compared to Yellow and Red-Yellow Latosols. YL presented the highest available water capacity among analyzed soils.